COVID-19 Lockdown in a Kenyan Informal Settlement: Impacts on Household Energy and Food Security - Shupler, Matthew; Mwitari, James; Gohole, Arthur; de Cuevas, Rachel Anderson; Puzzolo, Elisa; Čukić, Iva; Nix, Emily; Pope, Dan (Cold Spring Harbor Laboratory Press, 2020)
A COVID-19 lockdown may impact household fuel use and food security for ~700 million subSaharan Africans who rely on polluting fuels (e.g. wood, kerosene) for household energy and typically work in the informal economy. In an informal settlement in Nairobi, surveys administered before (n=474) and after (n=194) a mandatory COVID-19-related community lockdown documented socioeconomic/household energy impacts. During lockdown, 95% of participants indicated income decline or cessation and 88% reported being food insecure. Three quarters of participants cooked less frequently and half altered their diet. One quarter (27%) of households primarily using liquefied petroleum gas (LPG) for cooking before lockdown switched to kerosene (14%) or wood (13%). These results indicate the livelihoods of urban Kenyan families were deleteriously affected by COVID-19 lockdown, with a likely rise in household air pollution from community-level increases in polluting fuel use. To safeguard public health, policies should prioritize enhancing clean fuel and food access among the urban poor.
This preprint from MedRxiv is now published in Renewable and Sustainable Energy Reviews doi: 10.1016/j.rser.2021.111018
Keywords: Clean cooking; Household energy; COVID-19; Air pollution; Nairobi; Informal urban settlement; Food security